(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Screen-house and field experiments were carried out to evaluate and compare the activities of Root grow (mycorrhiza fungi) and broiler droppings (singly and both) on root-knot nematode, Meloidogyne incognita infecting Cucumber, Cucumis sativus (L). The experiment was designed as a 2 by 5 factorial fitted into a Complete Randomised Design (CRD) and Randomized Complete Block Design (RCBD) for screen house and field experiments respectively. Two levels each of the two treatments were evaluated both in the screen house and on the field. Root-grow (mycorrhiza fungi) was evaluated at the rate of 0.5 g and 1.0 g while broiler droppings were evaluated at the rate of 50 g and 100 g. The effects of treatments on vegetative growth as well as nematode damage and population were determined both in the screen house and on the field. All data collected were subjected to Analysis of Variance (ANOVA) and where treatment means were significant, multiple comparisons of treatments were done using Tukey’s honesty significant difference at a 5 % level of significance. Broiler droppings at 100 g and 50 g were more effective in controlling nematode than the two levels of Root grow (mycorrhiza fungi). Plant growth was best with broiler droppings at 100 g followed by broiler droppings at 50 g. Nematode population was reduced in all plant treated and were less galled compared with the control. The results showed that broiler droppings and mycorrhiza fungi can be used in controlling root-knot nematode Meloidogyne incognita on cucumber